The illusion of peace : - Marks, Sally (Palgrave Macmillan, 2003)
Balancing discussions of high politics, economics, and ethnic and nationalist rivalries, historian Marks explores the failure of the European elites to establish workable institutions to ensure the peace in the years during World War II. She argues that reluctance to decisively confront Germany and the Soviet Union as they grew stronger during the interwar years, combined with an ill-advised disarmament process and ethnic instabilities, contributed to the inevitability of war. This is a revised edition of a work first published in 1976, but Marks does not explicitly note what changes were made.